The Potentials and Development of the One District One Product in Luang Prabang Capital - SIOUDOMPHAN, Soutthavone; INTHAVICHIT, Lattana; SONESAI, Khamsone; KINGSADA, Youtthasack; DUANGPASITH, Phatsa; SEANGCHAN, Vilaxay; PHANTHOUAMATH, Phoutthalack (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aims to examine the capability of producing and developing products for official acceptance of One District One Product (ODOP) of local people in Luang Prabang Capital; examine the factors that relate to the capability in producing and developing products for acceptance of ODOP of local people in Luang Prabang Capital; and analyze the trends in producing and developing products for acceptance of ODOP of local people in Luang Prabang Capital. The result of this study will be useful for many sectors such as producers in terms of production and development, for policy makers in terms of supporting production and development products in ODOP campaign concept in Luang Prangbang as well as in Lao PDR. The result shows that the local people have high capability level in producing and developing products for ODOP registration whose products are hand-made focused, unique, and reflect Lao traditional characteristics, especially the Luang Prabang people. The products are made of raw materials from nature and are designed by local wisdom which traditional pattern is adapted to match the contemporary trend and to qualify the ODOP requirement of Lao PDR. The result of the hypothetical test shows that factors of production, product value, returns, ODOP recognition by the people, and production experience have positive relations with the capability of producing and developing products for ODOP registration of local people in Luang Prabang with significance value of 0.05. In terms of the trend in producing and developing products for ODOP requirements, it tends to increase by 87.8%. They are to focus on the products’ uniqueness and on the customers’ preferences. They also concentrate on product images and branding, product development and packaging.